Éduquer le locus de contrôle vocationnel par le truchement des croyances - Fournier, Geneviève; St-Onge, Susan (Canadian Journal of Counselling and Psychotherapy, 2007)
This article presents a synthesis of the theoretical foundations that brought us to investigate the principal vocational beliefs of individuals having difficulty with their approach to socio-professional insertion, as well as the particular viewpoint from which we have investigated them. A survey of our main results and particularly the typology of the vocational beliefs that we have derived, is also proposed. From this discussion ensues the presentation of the principles of intervention developed by us to help young adults facing difficulty in their socio-professional insertion.